2014
DOI: 10.1136/bjsports-2013-093312
|View full text |Cite
|
Sign up to set email alerts
|

Hip chondropathy at arthroscopy: prevalence and relationship to labral pathology, femoroacetabular impingement and patient-reported outcomes

Abstract: Chondropathy was prevalent, and associated with increasing age, coexisting labral pathology or FAI. Severe chondropathy was associated with worse pain and function at 18 months postsurgery. Little improvements were observed in participants over a further 12 months, regardless of chondropathy status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
117
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(122 citation statements)
references
References 47 publications
3
117
1
1
Order By: Relevance
“…18,24 Moreover, patients with chondrolabral pathology have reduced patient-reported outcomes (PROs) for up to 3 years post hip arthroscopy. 23 Impairments of physical function in this postoperative patient group may also be present postoperatively but have never been evaluated. In addition, our previous studies have shown that age and chondropathy severity affect PRO scores, 22,23 and these factors should be considered when examining outcomes and impairments in patients with chondrolabral pathology.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…18,24 Moreover, patients with chondrolabral pathology have reduced patient-reported outcomes (PROs) for up to 3 years post hip arthroscopy. 23 Impairments of physical function in this postoperative patient group may also be present postoperatively but have never been evaluated. In addition, our previous studies have shown that age and chondropathy severity affect PRO scores, 22,23 and these factors should be considered when examining outcomes and impairments in patients with chondrolabral pathology.…”
mentioning
confidence: 99%
“…23 Impairments of physical function in this postoperative patient group may also be present postoperatively but have never been evaluated. In addition, our previous studies have shown that age and chondropathy severity affect PRO scores, 22,23 and these factors should be considered when examining outcomes and impairments in patients with chondrolabral pathology. As impairments in functional tasks, such as hopping distance and endurance in rising to standing on 1 leg, may ex-…”
mentioning
confidence: 99%
See 3 more Smart Citations